112k views
5 votes
Help on #51 please !!

Help on #51 please !!-example-1
User Hamoudaq
by
5.9k points

1 Answer

2 votes

Answer:

53. ±6

51. 2

Explanation:

According to the Order of Operations [GEMS\BOMDAS\PEMDAS etc.], in this case, evaluate everything in grouping symbols first, then evaluate the exponents to avoid confusion:


\sqrt{(32 + {2}^(3) - 4)} = √(32 + 8 - 4) = √(36) = ±6 \\ \\ (17 - 11 + {4}^(2)) / 11 = (17 - 11 + 16) / 11 = \\ \\ 22 / 11 = 2

I am joyous to assist you anytime.

User TMBT
by
5.9k points